Differential roles of MAPK kinases MKK3 and MKK6 in osteoclastogenesis and bone loss - Boyle, David L.; Hammaker, Deepa; Edgar, Meghan; Zaiss, Mario M.; Teufel, Stefan; David, Jean Pierre; Schett, Georg; Firestein, Gary S. (PLoS ONE, 2014)
Bone mass is maintained by osteoclasts that resorb bone and osteoblasts that promote matrix deposition and mineralization. Bone homeostasis is altered in chronic inflammation as well as in post-menopausal loss of estrogen, which favors osteoclast activity that leads to osteoporosis. The MAPK p38? is a key regulator of bone loss and p38 inhibitors preserve bone mass by inhibiting osteoclastogenesis. p38 function is regulated by two upstream MAPK kinases, namely MKK3 and MKK6. The goal of this study was to assess the effect of MKK3- or MKK6-deficiency on osteoclastogenesis in vitro and on bone loss in ovariectomy-induced osteoporosis in mice. We demonstrated that MKK3 but not MKK6, regulates osteoclast differentiation from bone marrow cells in vitro. Expression of NFATc1, a master transcription factor in osteoclastogenesis, is decreased in cells lacking MKK3 but not MKK6. Expression of osteoclast-specific genes Cathepsin K, osteoclast-associated receptor and MMP9, was inhibited in MKK3-/- cells. The effect of MKK-deficiency on ovariectomy-induced bone loss was then evaluated in female WT, MKK3-/- and MKK6-/- mice by micro-CT analysis. Bone loss was partially inhibited in MKK3-/- as well as MKK6-/- mice, despite normal osteoclastogenesis in MKK6-/- cells. This correlated with the lower osteoclast numbers in the MKK-deficient ovariectomized mice. These studies suggest that MKK3 and MKK6 differentially regulate bone loss due to estrogen withdrawal. MKK3 directly mediates osteoclastogenesis while MKK6 likely contributes to pro-inflammatory cytokine production that promotes osteoclast formation.
EVALuna2:12931